Diseño y construcción de un prototipo de máquina cosechadora especializada en grano de quinua como propuesta comercial (2022)
Currently, processes such as quinoa harvesting are carried out manually, which affects the efficiency of the process, generating economic losses, and there is also a lack of nationally manufactured technology that adapts to the budget of farmers and the topography of the region